Penggunaan media pembelajaran Quizizz untuk meningkatkan motivasi belajar peserta didik dalam memahami teks informatif di Sekolah Dasar - Shakina Aulia Rachmawati; St Y Slamet; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2025)
This study aims to enhance student motivation in understanding informative texts through the use of Quizizz learning media at SDN 2 Barenglor. The research method employed is Classroom Action Research (CAR). Data collection techniques include observation, self reports, and tests in the form of evaluation questions for students via Quizizz. Validity testing techniques involve source triangulation and method triangulation. The data analysis technique used in this study is comparative descriptive analysis, derived from the results of observations in Cycle I and Cycle II. The researcher also employs interactive data analysis as proposed by Miles and Huberman. The results of this study conclude that the use of Quizizz as a learning medium can enhance students' motivation to learn and understand informational texts at SDN 2 Barenglor. This success is marked by a significant increase in test results from evaluation questions using Quizizz, with a rise of 28% from cycle I to cycle II, from 60% to 88%. This percentage has reached the target achievement indicators of the learning objectives, which is 75% or MMC (Minimum Mastery Criteria) of 75. Furthermore, the analysis of students' motivation to learn from cycle I to cycle II shows a significant increase. In cycle I, students' motivation was categorized as